1977
DOI: 10.1001/archderm.113.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal scalded skin syndrome. Clinical features, pathogenesis, and recent microbiological and biochemical developments

Abstract: The essential clinical features of staphylococcal scalded skin syndrome (SSSS) and otherforms of toxic epidermal necrolysis (TEN) are contrasted. Whereas TEN is a devastating disease of multiple causes and of high fatality affecting all age groups, SSSS comprises many clinical entitles that occur primarily in early childhood and is caused by certain phage group 2 staphylococci. Because of the high cleavage plane, the barrier is only translently perturbed, and rapid recovery is the rule. Although the early stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0
3

Year Published

1977
1977
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 71 publications
3
33
0
3
Order By: Relevance
“…'l However, addition of protease inhibitors to both in-vitro and in-vivo models of epidermolysis failed to inhibit epidermal splitting". [53][54][55] and, until the demonstration of similarities between ET and serine protease (see below), it was agreed generally that ET had no proteolytic activity.…”
Section: Discovery Isolation and Properties Of Et (Epidermolytic Toxin)mentioning
confidence: 99%
“…'l However, addition of protease inhibitors to both in-vitro and in-vivo models of epidermolysis failed to inhibit epidermal splitting". [53][54][55] and, until the demonstration of similarities between ET and serine protease (see below), it was agreed generally that ET had no proteolytic activity.…”
Section: Discovery Isolation and Properties Of Et (Epidermolytic Toxin)mentioning
confidence: 99%
“…Serologically, ETs involved in human diseases mainly consist of two types, ETA and ETB (6,27). Both toxins cause intraepidermal cleavage through the granular layer, without epidermal necrolysis or an inflammatory response of the skin (6,19,27). Several lines of evidence have suggested that ETs act as serine proteases to induce intraepidermal cleavage: (i) amino acid sequences of ETA and ETB show similarity with the S. aureus V8 serine protease (17), and the catalytic site of V8 protease is conserved in ETA (7); (ii) partially purified ETs preincubated with serine protease inhibitors exhibit delayed skin exfoliation (17); (iii) replacement of the serine residue with glycine in the putative catalytic site of ETA completely abolishes the exfoliative activity of the toxin (35,38); and (iv) crystal structures of ETA (13,53) and ETB (52) have recently been determined, and both types were shown to structurally belong to the chymotrypsin family of serine proteases.…”
mentioning
confidence: 99%
“…The complex of skin lesions called the staphylococcal scalded skin syndrome in humans (7,10,16) has several aspects in common with exudative epidermitis in pigs. Staphylococcal scalded skin syndrome is caused by infection with Staphylococcus aureus strains that produce exfoliative toxin ETA, ETB, or both (14).…”
mentioning
confidence: 99%